Cercarial behavior determines risk of predation - Selbach, Christian; Rosenkranz, Micha; Poulin, Robert (Journal of parasitology, 2019)
The potential for local biodiversity to affect transmission success of parasites has been shown to be particularly important in trematodes, where non-host organisms can feed on and ‘dilute’ free-living infective stages (cercariae). Earlier studies have analyzed the effects of various predators on transmission stages of single trematode species, but not how cercariae of different species react to predation pressure. Here, we tested whether cercariae with different host-searching movement patterns show varying susceptibility to predation by non-host species with different feeding habits. For this study, we performed a set of predation experiments with 6 species of trematode cercariae (Coitocaecum parvum, Maritrema poulini, Apatemon sp., Telogaster opisthorchis, Plagiorchioid sp. I, and Aporocotylid sp. II) that represent 2 groups of host-searching behavior, free-swimming vs. bottom-dwelling, and 2 predators (Sphaerium sp., Physa acuta) with distinct feeding modes, a filter feeder and a grazer. Our results show that cercarial susceptibility to predation is highly dependent on the interspecific interaction between dispersal behavior of cercariae and feeding behavior of non-host organisms: Filter feeders only diluted free-swimming cercarial stages, not bottom-dwelling ones; grazers on the other hand, had no effect on free-swimming cercariae but reduced bottom-dwelling cercariae in 1 trematode species. Our findings give further support to the hypothesis that the transmission dynamics of trematodes do not simply depend on local biodiversity but rather on the species-specific interactions between parasite transmission stages and free-living organisms in the ecosystem. This has important implications for disease dynamics in ecological communities (e.g., the parasites' infection success), and for ecosystem energetics, as cercariae constitute important food items.
Gesehen am 24.03.2020